Leverage , Ukuran Perusahaan , Likuiditas Terhadap Profitabilitas Perusahaan Farmasi di BEI Periode 2012 - 2018 - Ristiani, Aulia Vivi; Nurlaela, Siti; Dewi, Riana Rachmawati (Universitas Nusantara PGRI Kediri, 2020)
This study aims2 to examine2 and analyze2 the2 effect2 of leverage (DER), company size (SIZE), liquidity (CR) on the1 profitability of pharmaceutical companies on2 the2 Indonesian Stock2 Exchange2 in the period 2012 - 2018. The population1 in1 this1 study1 is pharmaceutical companies1 listed1 on1 the Indonesian Stock1 Exchange1 in the 2012-2018 period. Sampling uses a purposive sampling technique, so that a sample of 7 pharmaceutical companies is obtained. Data collection is carried out using documentation techniques obtained from the official website www.idx.co.id .The data analysis2 technique2 used2 is multiple2 linear1 regression1 analysis. The results1 of1 this study indicate that leverage, company size and liquidity simultaneously affect profitability while partially leverage influences profitability as well as company size and liquidity affect the profitability of pharmaceutical companies.